Streptococcus gallolyticus Increases Expression and Activity of Aryl Hydrocarbon Receptor-Dependent CYP1 Biotransformation Capacity in Colorectal Epithelial Cells - Taddese, Rahwa; Roelofs, Rian; Draper, Derk; Wu, Xinqun; Wu, Shaoguang; Swinkels, Dorine W.; Tjalsma, Harold; Boleij, Annemarie (Frontiers in Cellular and Infection Microbiology, 2021)
Objective: The opportunistic pathogen Streptococcus gallolyticus is one of the few intestinal bacteria that has been consistently linked to colorectal cancer (CRC). This study aimed to identify novel S. gallolyticus-induced pathways in colon epithelial cells that could further explain how S. gallolyticus contributes to CRC development. Design & Results: Transcription profiling of in vitro cultured CRC cells that were exposed to S. gallolyticus revealed the specific induction of oxidoreductase pathways. Most prominently CYP1A and ALDH1 genes that encode phase I biotransformation enzymes responsible for detoxification or bio-activation of toxic compounds. A common feature is that these enzymes are induced though the Aryl hydrocarbon receptor (AhR). Using the specific inhibitor CH223191, we showed that the induction of CYP1A was dependent on the AhR both in vitro using multiple CRC cell lines as in vivo using wild-type C57bl6 mice colonized with S. gallolyticus. Furthermore, we showed that CYP1 could also be induced by other intestinal bacteria and that an of yet unidentified diffusible factor from the S. galloltyicus secretome (SGS) induces CYP1A enzyme activity in an AhR-dependent manner. Importantly, priming CRC cells with SGS increased the DNA damaging effect of the polycyclic aromatic hydrocarbon 3-methylcholanthrene. Conclusion: This study shows that gut bacteria have the potential to modulate the expression of biotransformation pathways in colonic epithelial cells in an AhR-dependent manner. This offers a novel theory on the contribution of intestinal bacteria to the etiology of CRC by modifying the capacity of intestinal epithelial or (pre-)cancerous cells to (de)toxify dietary components, which could alter intestinal susceptibility to DNA damaging events.